Rancang Bangun Sistem Pengolahan Data Cuti Karyawan Berbasis Web Pada PT Care Spunbond - Handayani, Indri; Hidayat, Irfan; Amaliyah, Ghina (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2023)
Data processing at PT Care Spunbond already uses semi-computerization, but in recording leave data processing still uses a leave form in the form of HVS paper as the medium and is processed or inputted into Microsoft Excel, causing several problems (constraints) including a long time in terms of making reports because (must recap the data on the results of one leave application) one by one must recap the results of the data for submitting leave (applications for leave). Looking at the problems faced, it is very necessary to have a system that makes it easier to make reports so that it doesn't take a long time, the process of submitting leave and inputting results becomes easier, and providing up-to-date report information, as well as minimizing errors in reporting.